A dyadic perspective of socially responsible mechanisms for retailer-manufacturer relationship in an apparel industry. Issue 3 (31st December 2018) - Yadlapalli, Aswini; Rahman, Shams; Rogers, Helen
Abstract : Purpose: The purpose of this paper is to identify and prioritise social responsible mechanisms in apparel supply chains to extend social responsibility from large retailers in developed countries to producers in developing nations. Design/methodology/approach: A framework that consists of supplier qualification and supplier relational mechanisms as two socially responsible mechanisms, with five factors and 18 dimensions is proposed. To prioritise the dimensions, analytic hierarchy process is employed by using a case study methodology of a major Australian retailer sourcing from Bangladesh manufacturers. Findings: Results indicate that at the mechanism level, both retailer and manufacturers perceive qualification of manufacturer as by far the most critical element compared to the relational mechanism. However, substantial differences exist at the factor level; namely, that the social factor is critical for the retailer, whereas the economic factor is critical for the manufacturer. Within the relational mechanism, evaluation helps retailers to enforce social responsibility, while manufacturers believe collaboration helps. Research limitations/implications: The major limitation of this study is the generalisation of the findings. The results obtained by focusing on a particular context in the Australian retail sector importing from Bangladesh, may not be applicable to other nations. Practical implications: By highlighting the difference of opinion, this study assists managers in developing guidelines to better understand the socially responsible mechanisms in the retailer-manufacturer dyadic relationship and to propose strategies to address the differences. Originality/value: This study advances the literature on inter-organisational relationship to retailer-manufacturer dyad for the implementation of social responsibility by including supplier qualification along with supplier relational mechanism.